2002
DOI: 10.1001/archneur.59.5.766
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intravenous Immunoglobulin in Patients With IgG Monoclonal Gammopathy and Polyneuropathy

Abstract: Intravenous immunoglobulin therapy was beneficial in 8 (40%) of our 20 patients with polyneuropathy and IgG monoclonal gammopathy of undetermined significance. Proximal leg weakness, short duration of symptoms, and demyelinating features on electrodiagnostic studies were associated with a response to IVIG therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 32 publications
0
19
0
3
Order By: Relevance
“…Patients were diagnosed with MGUSN when immunoglobulin (Ig)M or IgG was detectable in the serum, with and without antineural antibodies 29, 30. Due to the small sample size, MGUSN patients were subsumed into the CIDP group for further analysis as per previous suggestions 29, 31, 32…”
Section: Methodsmentioning
confidence: 99%
“…Patients were diagnosed with MGUSN when immunoglobulin (Ig)M or IgG was detectable in the serum, with and without antineural antibodies 29, 30. Due to the small sample size, MGUSN patients were subsumed into the CIDP group for further analysis as per previous suggestions 29, 31, 32…”
Section: Methodsmentioning
confidence: 99%
“…39 From these Class I studies we can conclude that IVIG benefits only a minority of patients with the neuropathy associated with IgM paraproteinemia. Gorson et al 40 reported more encouraging results describing improvement in 40% of patients with the neuropathy associated with an IgG monoclonal protein after receiving IVIG.…”
Section: Monoclonal Gammopathy Of Undetermined Significance-associatementioning
confidence: 99%
“…A cumulative dose of 2 g/kg body weight IVIg was applied under which 10 out of 25 patients improved within 2 weeks in the first trial [77], whereas in the other only two out of 11 patients exhibited clinical amelioration after 3 months [78]. A retrospective analysis of 20 patients with IgG-MGUS revealed an improvement in eight out of 20 patients studied after a full cycle of 2 g/kg IVIg [79].…”
Section: Polyneuropathy Associated With Monoclonal Gammopathymentioning
confidence: 99%